2006
DOI: 10.1002/chem.200600110
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenation of Duplex and Single‐Stranded d(CGGCCG) by Organometallic Anticancer Complexes

Abstract: We have studied the interaction of the organometallic anticancer ruthenium(II) complexes [(eta(6)-p-cymene)Ru(en)Cl][PF(6)] (1) and [(eta(6)-biphenyl)Ru(en)Cl][PF(6)] (2) (en=ethylenediamine) with the single-stranded (ss) DNA hexamer d(CGGCCG) (I) and the duplex d(CGGCCG)(2) (II) by HPLC, ESI-MS, and one- and two-dimensional (1)H and (15)N NMR spectroscopy. For ss-DNA, all three G's are readily ruthenated with [(eta(6)-arene)Ru(en)](2+), but for duplex DNA there is preferential ruthenation of G3 and G6, and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
94
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 79 publications
(102 citation statements)
references
References 34 publications
6
94
2
Order By: Relevance
“…Reactions between (η 6 -arene)Ru(ethylenediamine) species and DNA [16][17][18], serum proteins, peptides and amino acids [19][20], suggest that DNA is the favored target in living cells, specifically through metal binding at guanine N-7 [21]. DNA intercalation by these Ru II complexes is also feasible, both by arene pendant flat moieties [22], and by an aromatic substituent in the chelating ligand [23].…”
Section: Introductionmentioning
confidence: 96%
“…Reactions between (η 6 -arene)Ru(ethylenediamine) species and DNA [16][17][18], serum proteins, peptides and amino acids [19][20], suggest that DNA is the favored target in living cells, specifically through metal binding at guanine N-7 [21]. DNA intercalation by these Ru II complexes is also feasible, both by arene pendant flat moieties [22], and by an aromatic substituent in the chelating ligand [23].…”
Section: Introductionmentioning
confidence: 96%
“…The circular dichroism data also suggest that intercalation and/or minor groove binding to calf thymus DNA are involved in the binding of the bip and anthracene derivatives, but not the cym complex [82]. These data have been also confirmed by NMR studies [83]. More recent studies [84] have revealed unique modes of binding of the anticancer complex [( 6 -bip)Ru(en)Cl] + to the 14-mer DNA duplex III:…”
Section: Metal Arene Complexesmentioning
confidence: 77%
“…b) The aza-pyridine compounds, in which different isomers show significantly different cytostatic activity. [92][93][94] c) The organometallic half-sandwich compounds of formula [Ru(sandwich)(diamine)Cl], in which the amine ligand is an important factor for the activity; [95][96][97] also here hydrogen bonding plays an importance role.…”
Section: Ru Compounds and Mixed-metal Compoundsmentioning
confidence: 99%